2017
DOI: 10.1002/bkcs.11089
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Anti‐inflammatory, and Arginase Inhibitory Activity of Piceatannol and Its Analogs

Abstract: The present study describes the synthesis of piceatannol (2) and its analogs (3–8) using Wittig‐Horner reaction, Colvin rearrangement, and Sonogashira reaction as key steps and also evaluation of their inhibitory potency on the production of inflammatory mediator nitric oxide (NO) in lipopolysaccharide (LPS)‐induced RAW‐264.7 macrophages. Three compounds 7 (90.1%), 8 (60.8%), and 6 (55.2%) were found to potently inhibit NO production induced by LPS without affecting the viability of RAW‐264.7 cells. In additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Piceatannol (3,3′,4,5′-trans-tetrahydroxystilbene) is a natural stilbene found in fruits [8], seeds [9], and wine [10]. Piceatannol has been reported to have several beneficial properties, such as anti-oxidation [11], anti-inflammation [12], and neuroprotective activity [13]. The number and substituted position of hydroxys make piceatannol more preferentially active than other natural stilbene, such as resveratrol and oxyresveratrol [11].…”
Section: Introductionmentioning
confidence: 99%
“…Piceatannol (3,3′,4,5′-trans-tetrahydroxystilbene) is a natural stilbene found in fruits [8], seeds [9], and wine [10]. Piceatannol has been reported to have several beneficial properties, such as anti-oxidation [11], anti-inflammation [12], and neuroprotective activity [13]. The number and substituted position of hydroxys make piceatannol more preferentially active than other natural stilbene, such as resveratrol and oxyresveratrol [11].…”
Section: Introductionmentioning
confidence: 99%
“…PIC is similar to resveratrol (RES) and shares similar biological activities. It has been shown to possess various beneficial properties, including antioxidation, anti-inflammation, and neuroprotective activities [ 19 , 20 , 21 ]. Li’s research demonstrated that PIC could suppress inflammation induced by tumor necrosis factor-alpha (TNF-α) [ 22 ].…”
Section: Introductionmentioning
confidence: 99%